Deep water [videorecording (DVD)] - Stone, Yael; Taylor, Jeremy Lindsay (Acorn Media, 2017)
When the mutilated corpse of a young gay man is found in a smart Bondi Beach apartment, Detectives Tori Lustigman and Nick Manning are assigned the case. Is this brutal murder a domestic disturbance, a robbery gone wrong, or a gay hate crime? With mounting evidence to suggest the perpetrator has killed before, they start digging through old investigations and the discovery is shocking. They uncover up to 80 possible murders of gay men in New South Wales.